Predicting Adolescent Anxiety with Childhood Attachment Disruptions: A Systematic Review - Dr. Nabeela Sulaiman,; Shahid, Raheela (JECCE, 2025)
This systematic review explored the relationship between childhood attachment disruptions and the development of anxiety during adolescence. A structured search was conducted for studies from five major databases between 2000 and July 2024, selecting studies that longitudinally examined the association of childhood attachment with later anxiety in adolescence. Four studies meeting the inclusion criteria were analyzed to show that insecure, avoidant, and disorganized attachment styles within childhood predicted the emergence of adolescent anxiety. These results pointed to the clear association of attachment disruptions in early childhood with anxiety disorders later in life and, therefore, strengthened the efforts of early intervention in supporting the development of secure attachment to prevent later mental health problems, specifically anxiety. These findings showed that preventing insecure attachment in early childhood could be one potential strategy for preventing anxiety disorders later in adolescence.